(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The main purpose of this study was to investigate the relationship between brand experience and passenger’s behavioral intention. The study adopted a cross-sectional survey and 120 passengers of inter-state branded companies were the target population. The data was generated through a primary source and a closed ended questionnaire of five-point likert scale was administered to respondent. The study hypotheses were analyzed Pearson’s product moment with the aid of statistical package for social sciences (SPSS). The finding of the study revealed that, there is a strong and positive relationship between brand experience dimensions (safety, comfort, driver’s competence, travel time and vehicle cleanliness) with passengers’ behavioral intention. The study recommended that transport should make sure that they provide comfortable seats, screens and well air-conditioned vehicles to make the vehicle comfortable tor travelers. Again, that drivers should be well trained and must have a good geographical command.